Assessing migration through social media: a review. Issue 2 (3rd April 2019) - Righi, Alessandra
ABSTRACT: Social media can be used not only for evaluating migration flows almost in real time and the degree of integration in the destination countries but also for the understanding of public opinion sentiment about immigration. Experiences based on scraping social media are reviewed, and the use of geo-located data and advertising platforms turns out to be the most promising opportunities supplied by these sources. The current challenge is to measure the sentiment of Italian-speaking twitterers toward migration.